2011
DOI: 10.1186/1749-8090-6-120
|View full text |Cite
|
Sign up to set email alerts
|

Thrombotic gene polymorphisms and postoperative outcome after coronary artery bypass graft surgery

Abstract: BackgroundEmerging perioperative genomics may influence the direction of risk assessment and surgical strategies in cardiac surgery. The aim of this study was to investigate whether single nucleotide polymorphisms (SNP) affect the clinical presentation and predispose to increased risk for postoperative adverse events in patients undergoing coronary artery bypass grafting surgery (CABG).MethodsA total of 220 patients undergoing first-time CABG between January 2005 and May 2008 were screened for factor V gene G1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
0
8
0
2
Order By: Relevance
“…The incidence of thromboembolic complications during perioperative and postoperative period in cardiac surgical patients was related with heterozygous FVL mutation [16]. In MTHFR C677T MTHFR A1298C PT G20210A FVL HET HET WT WT HET HET WT HET HET HET WT HET HET HET WT HET HET HET WT WT HET HET HET WT HET HET WT WT HET HET WT WT HET HET WT WT HET HET WT HET HET HET WT WT HET HET WT WT HET HET WT WT HET HET HET WT FVL=Factor V Leiden, PT 20210A=Prothrombin gene mutation, MTHFR=Methylenetetrahydrofolate reductase, HET=heterozygous, WT=wild type # contrast, Emiroglu et al [13] did not find a statistically significant difference with postoperative thromboembolic complications, which may be due to routine heparin administration postoperatively. In contrast to the report of Emiroglu et al [13], Donahue et al [15] reported that postoperative bleeding drainage was statistically lower in patients with FVL mutation compared with non-carriers.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of thromboembolic complications during perioperative and postoperative period in cardiac surgical patients was related with heterozygous FVL mutation [16]. In MTHFR C677T MTHFR A1298C PT G20210A FVL HET HET WT WT HET HET WT HET HET HET WT HET HET HET WT HET HET HET WT WT HET HET HET WT HET HET WT WT HET HET WT WT HET HET WT WT HET HET WT HET HET HET WT WT HET HET WT WT HET HET WT WT HET HET HET WT FVL=Factor V Leiden, PT 20210A=Prothrombin gene mutation, MTHFR=Methylenetetrahydrofolate reductase, HET=heterozygous, WT=wild type # contrast, Emiroglu et al [13] did not find a statistically significant difference with postoperative thromboembolic complications, which may be due to routine heparin administration postoperatively. In contrast to the report of Emiroglu et al [13], Donahue et al [15] reported that postoperative bleeding drainage was statistically lower in patients with FVL mutation compared with non-carriers.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 The reasons for failure of the test agent in these studies remain unclear; however, variability in clinical outcomes across a range of patient-level factors, including race and sex, was observed in these large multicenter studies. There are few prior reports describing genetic association studies in vein bypass outcomes, 29-31 and none involving peripheral grafting. Importantly, our study was not a broad exploratory investigation of genetic associations but rather a hypothesis-based testing of a single suspected genetic marker based on the recent coronary studies.…”
Section: Discussionmentioning
confidence: 99%
“…Gene polymorphisms and/or genetic mutations as new markers of morbidity and mortality in patients after CABG have been intensively studied over the past few years ( 17 ). Numerous studies in this field have been based on the identification of single nucleotide polymorphisms (SNPs) in candidate genes regulating inflammatory response ( 18 , 19 ), thrombotic pathways ( 20 , 21 ), oxidative stress ( 11 ), renin–angiotensin system ( 22 , 23 ), cell damage ( 24 , 25 ), and their association with post-operative results in patients undergoing CABG. The studies published so far and described in Tables S1–S5 in Supplementary Material based on specific pathways, have addressed two main questions: (1) can gene polymorphisms or mutations modulate or affect plasma levels of a dynamic biomarker, both at baseline or after the stimulus resulting from cardiac surgery?…”
Section: Genetic Markersmentioning
confidence: 99%
“…However, we have reliable data regarding two markers: fibrinogen ( 23 , 27 ), which is between inflammation and hemostasis; and beta-thromboglobulin ( 21 ). Interestingly, only one study has addressed the main issue of graft patency after CABG by assessing the presence of factor V Leiden genetic mutations ( 22 ). This study, limited by the small number of patients enrolled (a total of 100 CABGs), has suggested that the mutation Arg 506 Gln tends to be associated with saphenous graft occlusion [5/11 (45%) carriers vs. 18/89 (20%) non-carriers, p = 0.06] ( 32 ).…”
Section: Genetic Markersmentioning
confidence: 99%
See 1 more Smart Citation